Identifying Reading Comprehension Questions of National Examination for Senior High School Students - Nurul Hayati Daeli; Yenni Julia Ningsih Hutapea; Fitri Dian Ningsih Gea; Indah Lestari; Erikson Saragih (Journal of Languages and Language Teaching, 2020)
Reading is the complex cognitive process of decoding symbols to derive meaning. It is a form of language processing. Success in this process is measured as reading comprehension. The aim of the researcher is to identify the types of question reading comprehension of the national examination of the textbook. The form of this research is descriptive by analyzing the reading question in the Sonar Eksplorasi USBN/UNBK’s book 2019. Indicators data are grouped based on qualitative. To maintain the results of research carried out to collect data using descriptive qualitative. Then the data can be seen means out of reading comprehension questions into five types, namely question of literal comprehension, a question involving reorganization or reinterpretation, the question of inference, the question of evaluation and question of personal responses. The question of literal comprehension gets 5 data (5,05%). The next types are the question involving reorganization or reinterpretation it gets 6 data (6, 06%). The question of inference gets 5 data (5,05%). The question of evaluation gets 4 data (4, 04%). The last type is the question of personal responses which gets 10 (10, 10%).  Data obtained through book evaluation text by looking at the form and level of questions.  Based on this result, it can be concluded that the dominant type of used test is multiple-choice items in testing the reading comprehension.